REPRESENTATION OF ACTION MODIFIERS IN THE ENGLISH AND UZBEK LANGUAGES IN LITERARY DISCOURSE - Uzokova, Shakhnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
In world linguistics, scientific research is consistently carried out to clarify the patterns of the modification process in literary discourse and its application in communication, and to analyze language methods that implement the communicative goal in the cognitive-pragmatic and linguocultural areas. This article aims to identify the functional and semantic features of action modifiers in literary discourse in the English and Uzbek languages. The action modification in the discourse was studied as a cognitive process, and functional-semantic analysis of the language units that act as action modifiers in English and Uzbek was carried out. In addition, the nature of the similarities and differences in the features of action modifiers characteristic of different languages was substantiated. As a result, the pragmatic effectiveness of these linguistic elements was demonstrated by studying the functionality and semantic properties of action modifiers in artistic discourse.
Keywords: linguistic representation of the world; modification; prepositive modification; post-positive modification; literary discourse; action modifiers; distant modifier